Baltic Journal of Psychology; Volume 3, Number 1 - University of Latvia. Department of Psychology; Miezīte, Solveiga; Raščevska, Malgožata (University of Latvia. Department of Psychology, 2002)
Contents Editorial REPORTS OF EMPIRICAL STUDIES Psiholoģiskā separācija mātes meitas attiecībās pieaugušo vecumā / Anika Miltuze ...6 Adult Attachment Styles, Childhood Abuse Experience and Violence in Intimate Relationships / leva Bite ...19 The psychological Adjustment of Children with Phenylketonuria / Roma Jusiene, Rasa Bieliauskaite, Loreta Cimbalistiene,Vaidutis Kucinskas .. 34 Psychosocial Factors and Smoking Behaviour in a Latvian Adolescent Population / Sandra Sagrati, Hester Dunlap, Solveiga Miezitis, Ieva Ranka... 41 The Attribution Style Questionnaire (Lithuanian version): Adaptation Study Comparing Depressed with Nondepressed Participants / Viktoras Keturakis ...55 Dimensionality of Pay Satisfaction in Latvia: Exploring Structure / Uldis Pavuls ...63 THEORETICAL ARTICLES Creativity and innovation: Men's business or women's work? / Arthur Cropley... 77 PROFESSIONAL AND ACADEMIC ISSUES IN PSYCHOLOGY IN BALTICS Psihologa profesijas standarts / Malgozata Rascevska, Inga Ezera, liāna Bistrova, Pāvels Tjurins, Ludmila Kaļiņņikova, Natālija Šmeļova, Geršons Breslavs, Guntis Tomsons, Tamāra Čaikovska, Kristīne Maslovska, Anda Kauliņa, Inese Platpīre, Ingūna Upzare, Evija Striķa, Anda Fenogenova ...89 Professional Standard ...96 OPEN DISCUSSION BY OUR READERS, AUTHORS, AND EDITORS Question: Which late twentieth century theories, concepts, and research directions could play a particularly significant role in psychology's future development? / Imants Baruss, Thomas Oakland, Juris G. Draguns, Viesturs Renge ...103 Notes on Authors... 106
Baltijas Psiholoģijas Žurnāls
Keywords: Research Subject Categories::SOCIAL SCIENCES::Social sciences::Psychology; Psiholoģija; Sociālā psiholoģija; Bērnu psiholoģija; Pusaudžu psiholoģija; Izglītības psiholoģija; Ģimeņu psiholoģija; Psihopatoloģija; Social psychology; Psychopathology; Child psychology; Educational psychology; Creativity; Adolescent psychology; Family psychology